Heat sink and method of manufacturing heat sink
Patent Information
- Application Number
- CN202580019346.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-05
- Filing Date
- 2025-02-28
- Publication Date
- 2026-10-09
AI Technical Summary
石墨等金属较硬且不易变形,因此作为散热片的适用范围受限
[0032]根据上述本发明的(1)~(20)方面,能够提供一种对散热对象具有形状追随性且散热性高的散热片和散热片的制造方法。
Smart Images

Figure CN122893408A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to heat sinks and methods for manufacturing heat sinks. Background Technology
[0002] Patent Document 1 discloses a heat sink made of graphite. Graphite and other metals are hard and not easily deformed, thus limiting their applicability as heat sinks. Furthermore, as disclosed in Patent Document 2, heat sinks made by mixing deformable liquid metal with polymers are known, but because the polymer is dominant, its low thermal conductivity prevents it from achieving sufficient heat dissipation.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-050725
[0006] Patent Document 2: Michael D. Bartlett, Navid Kazem, Matthew J. Powell-Palm, Xiaonan Huang, Wenhuan Sun, Jonathan A. Malen, and Carmel Majidi “Highthermal conductivity in soft elastomers with elongated liquid metalinclusions” Proceedings of the National Academy of Sciences (PNAS)<URL:https: / / www.pnas.org / doi / 10.1073 / pnas.1616377114> Summary of the Invention
[0007] The technical problem that the invention aims to solve
[0008] The purpose of this invention is to provide a heat sink with shape conformity to the heat dissipation object and high heat dissipation performance, and a method for manufacturing the heat sink.
[0009] Technical solutions for solving technical problems
[0010] To address the aforementioned problems, the invention disclosed in this application has multiple aspects, and the key points of the representative aspects are summarized below.
[0011] (1) A heat sink for releasing heat generated by a heat dissipation object, comprising: a liquid metal layer deformable at room temperature; and a sealing sheet for sealing the liquid metal layer.
[0012] (2) In the heat sink described in (1), the liquid metal layer and the sealing sheet are elastic and flexible.
[0013] (3) In the heat sink described in (1) or (2), the liquid metal layer contains gallium-based metal.
[0014] (4) In any one of (1) to (3), the liquid metal layer contains metal powder with low reactivity to the liquid metal contained in the liquid metal layer.
[0015] (5) In the heat sink described in (4), the thermal conductivity of the metal powder is higher than that of the liquid metal.
[0016] (6) In the heat sink described in (4) or (5), the metal powder is copper powder.
[0017] (7) In the heat sink described in (4) or (5), the metal powder comprises at least one of iron powder, nickel powder, tungsten powder, silver powder, platinum powder and gold powder.
[0018] (8) In the heat sink described in (6), the weight of the copper powder relative to the total weight of the liquid metal layer is less than 16 wt%.
[0019] (9) In the heat sink described in (6), the weight of the copper powder is less than 14 wt% relative to the total weight of the liquid metal layer.
[0020] (10) In the heat sink described in (6), the weight of the copper powder is less than 12 wt% relative to the total weight of the liquid metal layer.
[0021] (11) In the heat sink described in (6), the weight of the copper powder is less than 10 wt% relative to the total weight of the liquid metal layer.
[0022] (12) In the heat sink described in (6), the weight of the copper powder is less than 7 wt% relative to the total weight of the liquid metal layer.
[0023] (13) In the heat sink described in (6), the weight of the copper powder is less than 5 wt% relative to the total weight of the liquid metal layer.
[0024] (14) In any of (1) to (13) the heat sink is a polymer nanosheet that has a tight fit to the heat dissipation object.
[0025] (15) In any one of (1) to (14) the heat sink is made of styrene-butadiene-styrene block copolymer.
[0026] (16) In any of (1) to (15) the heat sink, the sealing sheet includes a first sealing layer covering the upper surface of the liquid metal layer and a second sealing layer covering the lower surface of the liquid metal layer, wherein the first sealing layer and the second sealing layer are tightly fitted together at the periphery of the liquid metal layer.
[0027] (17) In the heat sink described in (16), the film thickness of the first sealing layer and the second sealing layer is 100 nm or more and 500 nm or less.
[0028] (18) In the heat sink described in (1), the liquid metal layer comprises a eutectic metal of gallium (Ga), indium (In) and tin (Sn) (GaInSn) and copper powder in a weight ratio of less than 5% relative to the total weight of the liquid metal layer, the sealing sheet is made of styrene-butadiene-styrene block copolymer, the sealing sheet comprises a first sealing layer covering the upper surface of the liquid metal layer and a second sealing layer covering the lower surface of the liquid metal layer, the first sealing layer and the second sealing layer are tightly sealed at the periphery of the liquid metal layer, and the film thickness of the first sealing layer and the second sealing layer is more than 100 [nm] and less than 500 [nm].
[0029] (19) A method of manufacturing a heat sink for releasing heat generated by a heat dissipation object, comprising: a step of preparing a first sealing layer; a step of forming a frame portion on the first sealing layer in such a way as to surround an area to which liquid metal is to be coated; a step of coating the area with liquid metal; a step of extending the liquid metal coated in the area into a sheet shape in such a way as to correspond to the film thickness of the frame portion; a step of setting a second sealing layer in such a way as to sandwich the liquid metal together with the first sealing layer; a step of cutting the first sealing layer and the second sealing layer between the liquid metal and the frame portion to remove the portion forming the frame portion; and a step of sealing the first sealing layer and the second sealing layer together at the periphery of the liquid metal.
[0030] (20) In the method of manufacturing the heat sink described in (19), before the step of coating the liquid metal, a step of mixing metal powder in the liquid metal is included.
[0031] The effects of the invention
[0032] According to aspects (1) to (20) of the present invention described above, it is possible to provide a heat sink and a method for manufacturing the heat sink that have shape following properties and high heat dissipation performance for heat dissipation objects. Attached Figure Description
[0033] Figure 1AThis is a schematic cross-sectional view of the heat sink in this embodiment.
[0034] Figure 1B This is an exploded perspective view showing the heat sink of this embodiment.
[0035] Figure 2 This is a graph showing the experimental results, categorized by the copper powder content, illustrating the relationship between the number of days elapsed after mixing copper powder into GaInSn and the state of GaInSn containing copper powder.
[0036] Figure 3A This is a graph showing the thermal conductivity of GaInSn itself, the heat sink of this embodiment, and the heat sink of the comparative example.
[0037] Figure 3B This is a graph showing an example of test results differentiated by the content of copper powder.
[0038] Figure 4 It is a graph showing the relationship between the film thickness of the sealing sheet and the thermal conductivity of the heat sink.
[0039] Figure 5A This is a diagram showing the steps involved in manufacturing a heat sink.
[0040] Figure 5B This is a diagram showing the steps involved in manufacturing a heat sink.
[0041] Figure 6 This is a graph representing an example of the test results for evaluating the heat dissipation performance of a heat sink.
[0042] Figure 7 This is a diagram illustrating an example of test results for evaluating the heat dissipation performance of a heat sink. Detailed Implementation
[0043] Hereinafter, embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail based on the accompanying drawings.
[0044] [Overview of Heatsink 100]
[0045] Figure 1A This is a schematic cross-sectional view of the heat sink in this embodiment. Figure 1B This is an exploded perspective view showing the heat sink of this embodiment. For example... Figure 1A and Figure 1B As shown, the heat sink 100 includes a liquid metal layer 10 and a sealing sheet 20 that seals the liquid metal layer 10. Furthermore, in Figure 1A , Figure 1B And the following Figure 5A , Figure 5BIn order to facilitate understanding and explanation, the width, thickness, shape and other aspects of each part are schematically represented, but the present invention is not limited to these illustrations.
[0046] Heat sinks are known to use metals such as graphite, as disclosed in Patent Document 1. However, metals such as graphite are hard and not easily deformed, thus limiting their applicability as heat sinks. Therefore, in this embodiment, a deformable liquid metal is used as the heat dissipation metal.
[0047] However, considering the corrosiveness to other metals, the risk of short circuits due to leakage, and the impact on human health, direct use of liquid metal is difficult. Therefore, using a sheet to cover the liquid metal is considered. On the other hand, since liquid metal has relatively low thermal conductivity, if the sheet covering the liquid metal is too thick, sufficient heat dissipation cannot be achieved. Furthermore, in the heat sink made of a mixture of liquid metal and polymer disclosed in Patent Document 2, although the problem of corrosion can be solved by covering the liquid metal with polymer, according to the inventors' test results, its thermal conductivity drops to less than one-third of the thermal conductivity of the liquid metal itself.
[0048] Therefore, in this embodiment, a thin polymer nanosheet is used as the sealing sheet 20, and a structure is adopted in which the sealing sheet 20 seals the liquid metal. This suppresses problems such as corrosion to other metals, short circuits due to leakage, and harm to the human body, while also exhibiting shape-following properties and achieving high heat dissipation. Here, shape-following properties refer to the property of being able to deform to mimic the shape of the object being cooled, including flexibility and extensibility. Furthermore, the sealing sheet 20 is not limited to completely sealing the liquid metal; it is acceptable even if gaps exist, as long as it does not easily cause problems such as corrosion to other metals, short circuits due to leakage, or harm to the human body.
[0049] The heat sink 100 of this embodiment can be attached to the surface of heat dissipation objects (heat-generating elements) such as circuit boards and batteries of electronic devices. In addition, since the heat sink 100 has shape-following properties, it can also be used to dissipate heat generated by wearable devices and other flexible electronic devices that are worn on the human body.
[0050] The following describes specific examples of the liquid metal layer 10 and the sealing sheet 20 constituting the heat sink 100.
[0051] [Liquid Metal Layer 10]
[0052] In this embodiment, the liquid metal used as the material of the liquid metal layer 10 is a eutectic alloy of gallium (Ga), indium (In), and tin (Sn) (hereinafter referred to as GaInSn). However, it is not limited to this; the liquid metal can be any metal that is in a semi-solid state (paste state) at room temperature and has deformability such as flexibility and extensibility. That is, the liquid metal can be a metal with a melting point below room temperature (approximately 15 to 30°C). Examples of metals that can be the main components of the liquid metal include Ga (gallium, melting point 29.76°C), In (indium, melting point 156.60°C), Sn (tin, melting point 231.93°C), Pb (lead, melting point 327.46°C), and Bi (bismuth, melting point 271.40°C). In addition, the liquid metal can be an alloy of these metals such as GaInSn, GaIn, GaSn, and BiInSn.
[0053] like Figure 1A and 1B As shown, the liquid metal layer 10 can be sheet-like. This shape allows for heat conduction in the in-plane direction and heat release from the upper or lower surface, improving heat dissipation. In this embodiment, the thickness of the liquid metal layer 10 is set to 200 μm. However, it is not limited to this; the thickness of the liquid metal layer 10 can be 10 μm or more and 200 μm or less.
[0054] Here, because liquid metal GaInSn has high fluidity and poor wettability to the sealing sheet 20, it is difficult to coat the sealing sheet 20 to form a sheet. Therefore, in this embodiment, copper powder is mixed into GaInSn as a filler to reduce fluidity and improve wettability. Specifically, 5 wt% or 10 wt% of copper powder is mixed into GaInSn. Here, wt% (weight percentage) is the ratio of the weight of copper powder to the total weight of the liquid metal layer 10 (also referred to as content in this specification).
[0055] Figure 2 The results represent the experimental findings that show the relationship between the number of days after copper powder is mixed into GaInSn and the state of GaInSn containing copper powder, differentiated by the copper powder content.
[0056] like Figure 2 As shown, when the copper powder content is 5 wt%, GaInSn is in a liquid state on day 1, exhibiting high fluidity and poor wettability. Furthermore, when the copper powder content is 5 wt%, GaInSn becomes a paste state after day 3 and maintains this state until day 30.
[0057] When the copper powder content is 10wt%, GaInSn is in a paste state from day 1 and becomes solid on day 30.
[0058] When the copper powder content is 15wt%, GaInSn is in a paste state from day 1 and becomes solid on day 3.
[0059] The above experimental results show that when the copper powder content is low (or non-existent), it results in a liquefied state with poor wettability. Therefore, it is preferable to form the liquid metal layer 10 not solely from GaInSn, but also by mixing it with copper powder. On the other hand, when the copper powder content is high, it solidifies quickly. In the solidified state, it is difficult to coat the sealing sheet 20 to form a sheet. Figure 2 In the photograph, GaInSn mixed with 10wt% and 15wt% copper powder showed a solidified state on day 30, without spreading into sheets.
[0060] As can be seen from the above, the copper powder content should be 10 wt% or less to maintain the paste state for several days, and more preferably 5 wt% or less. Furthermore, since the copper powder content only needs to be greater than 0 wt%, it is preferably 1 wt% or more and 10 wt% or less. In addition, as long as the copper powder content is greater than 0 wt%, it can also be around 5 wt%, for example, 1 wt% or more and 7 wt% or less.
[0061] Furthermore, the improved wettability due to the mixing of copper powder can be attributed to the reaction between GaInSn and copper powder, forming an oxide layer. This oxide layer forms a paste that can be applied to the sealing sheet 20 to form a sheet. However, the presence of the oxide layer may lead to a decrease in thermal conductivity.
[0062] Figure 3A This is a graph showing the in-plane thermal conductivity of GaInSn itself, the heat sink of this embodiment, and the heat sink of the comparative example. (See graph for details.) Figure 3A As shown, based on the inventors' insights and experimental results, the in-plane thermal conductivity of GaInSn itself is 23.2 (W / m·K), while the in-plane thermal conductivity of the heat sink 100 with a copper powder content of 5 wt% is 19.8 (W / m·K), and the in-plane thermal conductivity of the heat sink 100 with a copper powder content of 10 wt% is 27.1 (W / m·K). Thus, in the heat sink 100 with a copper powder content of 5 wt%, the in-plane thermal conductivity is lower compared to GaInSn. This is believed to be due to the formation of oxide portions from the mixed copper powder and the covering effect of the sealing sheet 20.
[0063] However, heatsink 100 and Figure 3A Compared to the composite heatsink shown, it achieves more than 10 times the thermal conductivity, which can be considered sufficient for heat dissipation. For example... Figure 3A As shown, the thermal conductivity of the composite heat sink is 1.25 (W / m·K). Furthermore, the composite heat sink refers to a heat sink that the inventors of this application, based on the disclosure of Patent Document 2 above, is made by mixing liquid metal (GaInSn) and polymer (Ecoflex (registered trademark) 00-30) in equal proportions.
[0064] On the other hand, in the heat sink 100 with a copper powder content of 10 wt%, the thermal conductivity is higher than that of GaInSn. This is believed to be because the oxide portion formed by the oxidation of liquid metal acts as a layer surrounding the copper powder (hereinafter referred to as the oxide layer), and these oxide layers aggregate to form a heat conduction path composed of copper powder. That is, the thermal conductivity decreases when the oxide layer is discretely formed, but by increasing the copper powder content, the amount of oxide layer aggregation increases, thereby increasing the heat conduction path and increasing the thermal conductivity. Furthermore, as... Figure 3A As shown, GaInSn has a thermal conductivity of 23.2 (W / m·K), while the thermal conductivity of copper powder is approximately 400 (W / m·K). Therefore, the metal powder mixed into the liquid metal preferably has a higher thermal conductivity than the liquid metal.
[0065] Furthermore, the metal powder mixed into the liquid metal is not limited to copper; any metal powder with low corrosivity and reactivity to the liquid metal is acceptable. High reactivity with the liquid metal would lead to chemical reactions such as corrosion. Specifically, the metal powder can be any one of copper (Cu), iron (Fe), nickel (Ni), tungsten (W), silver (Ag), platinum (Pt), gold (Au), or a mixture thereof. Additionally, the powder mixed into the liquid metal is not limited to metals and can also be carbon (C). Moreover, a small particle size is preferred for easy mixing with the liquid metal. Specifically, the particle size of the metal powder can be around 10–25 μm. However, it is not limited to this; the particle size can also be in the nanometer range.
[0066] Figure 3B This is a graph representing an example of test results differentiated by the copper powder content. Specifically, in Figure 3B The top left side of the chart shows the relationship between the copper powder content and thermal diffusivity. Figure 3B The top right side of the graph shows the relationship between the copper powder content and the in-plane thermal conductivity. Figure 3B The lower left side of the chart represents the elongation of heat sink 100 when the copper powder content is 12 wt%. Figure 3B The right side of the bottom row indicates the elongation of heat sink 100 when the copper powder content is 16wt%.
[0067] according to Figure 3BThe curves at the top indicate that the preferred copper powder content is below 16 wt%. This is because, according to... Figure 3B The curves in the top row show that sufficient thermal diffusivity and in-plane thermal conductivity can be obtained when the copper powder content is between 1 wt% and 16 wt%.
[0068] In addition, according to Figure 3B The graph at the bottom shows that the copper powder content is preferably less than 16 wt%. When the copper powder content is 12 wt%, the elongation of the heat sink 100 is at most about 270%, meaning it can be stretched to about 3.7 times its original size, which can be considered sufficient elongation. On the other hand, when the copper powder content is 16 wt%, the elongation of the heat sink 100 cannot be considered sufficiently adequate. Thus, while increasing the copper powder content will improve thermal conductivity, it will decrease elongation.
[0069] according to Figure 3B The experimental results shown in the various graphs indicate that the copper powder content should be between 1 wt% and 16 wt%. Additionally, considering... Figure 2 As shown, when the copper powder content is 15 wt%, it easily reaches a solidified state. The copper powder content is preferably 1 wt% or more and 14 wt% or less. Alternatively, the copper powder content can be 1 wt% or more and 12 wt% or less. Alternatively, the copper powder content can be 1 wt% or more and 10 wt% or less. Alternatively, the copper powder content can be 1 wt% or more and 7 wt% or less. Alternatively, the copper powder content can be 1 wt% or more and 5 wt% or less. Alternatively, the copper powder content can be 1 wt% or more and 3 wt% or less.
[0070] [Sealing Plate 20]
[0071] like Figure 1B As shown, the sealing sheet 20 includes a sealing layer 21 covering the upper surface of the liquid metal layer 10 and a sealing layer 22 covering the lower surface of the liquid metal layer 10. The sealing layer 21 and the sealing layer 22 are tightly fitted together at the periphery of the liquid metal layer 10.
[0072] The sealing sheet 20 can be made of a thin, stretchable, and flexible material. In this embodiment, a polymer nanosheet made of SBS (styrene-butadiene-styrene block copolymer) is used as the sealing sheet 20. The SBS-based polymer nanosheet has high adhesion. Therefore, the heat sink 100 has good adhesion on its upper and lower surfaces, allowing it to be attached to the heat dissipation object without the need for adhesives or tapes.
[0073] Figure 4 It is a graph showing the relationship between the film thickness of the sealing sheet and the thermal conductivity of the heat sink. Figure 4The horizontal axis represents the film thickness of sealing layer 21 and sealing layer 22 in the sealing sheet 20 made of SBS material. Figure 4 The vertical axis represents the proportion of the thermal conductivity of the heat sink 100 when the thermal conductivity of GaInSn is 1. Additionally, Figure 4 The values represent the in-plane thermal conductivity and the through thermal conductivity, respectively. Figure 4 The relationship between the thickness of the sealing film and the thermal conductivity of the heat sink shown is based on known theoretical calculations.
[0074] like Figure 4 As shown, when the film thickness of sealing layer 21 and sealing layer 22 is greater than 1000 nm, the thermal conductivity in the in-plane direction decreases. Therefore, the film thickness of sealing layer 21 and sealing layer 22 can be less than 1000 nm.
[0075] Furthermore, when the film thickness of sealing layer 21 and sealing layer 22 is greater than 500 nm, the thermal conductivity in the vertical direction decreases sharply. Therefore, the film thickness of sealing layer 21 and sealing layer 22 can be less than 500 nm.
[0076] Furthermore, the thinness of sealing layers 21 and 22 is subject to technical limitations; it can be manufactured if it is 100 nm or more. Additionally, sealing layers 21 and 22, made of SBS, exhibit the property that the thinner the film thickness, the higher the adhesion. Therefore, the film thickness of sealing layers 21 and 22 can be 100 nm or more and 500 nm or less. Figure 4 (The range of the strip-shaped region). By fabricating sealing layer 21 and sealing layer 22 within this range, it is possible to maintain the thermal conductivity in the vertical direction at approximately 80% of that of GaInSn, while simultaneously making the thermal conductivity in the in-plane direction comparable to that of GaInSn, and also ensuring a tight seal.
[0077] Furthermore, the material of the sealing sheet 20 is not limited to SBS. The material of the sealing sheet 20 may also be, for example, (a) styrene-based elastomers, (b) silicone-based elastomers, (c) olefin-based elastomers, (d) polyurethane-based elastomers, (e) polyester-based elastomers, (f) polyamide-based elastomers, (g) acrylic elastomers, (h) rubber-modified epoxy resins, etc. These materials may be used individually or in combination of two or more.
[0078] (a) Styrene-based elastomers, in addition to the above-mentioned styrene-butadiene-styrene block copolymer (SBS), can also include styrene-ethylene-butene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene-propylene-styrene block copolymer (SEPS, a hydride of SIS), styrene-ethylene-propylene block copolymer (SEP, a hydride of styrene-isoprene block copolymer), styrene-isobutylene-styrene block copolymer (SIBS), polystyrene copolymer (PS), etc.
[0079] (b) Organosilicon elastomers are elastomers with organopolysiloxanes as the main component, such as polydimethylsiloxane (PDMS), polymethylphenylsiloxane, and polydiphenylsiloxane. They can also be products partially modified with vinyl, alkoxy, or other compounds. Organopolysiloxane films can be obtained, for example, by treating a main agent containing a siloxane compound with a curing agent to polymerize and / or crosslink it. The curing agent can be selected based on the type of the main reactive group of the main agent. When the main agent has a hydrosilyl group as the main reactive group, a compound with an alkenyl group can be used as the curing agent; when the main agent has an alkenyl group as the main reactive group, a compound with a hydrosilyl group can be used as the curing agent.
[0080] (c) As an olefin-based elastomer, examples include copolymers of α-olefins with 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-hexene, and 4-methyl-pentene. Specific examples include copolymers of non-conjugated dienes with 2 to 20 carbon atoms, such as ethylene-propylene copolymer (EPR), ethylene-propylene-diene copolymer (EPDM), dicyclopentadiene, 1,4-hexadiene, cyclooctadiene, methylene norbornene, ethylidene norbornene, butadiene, and isoprene, with α-olefins, as well as carboxyl-modified NBRs copolymerized with butadiene-acrylonitrile copolymers.
[0081] (d) Polyurethane elastomers include, for example, elastomers formed from structural units consisting of hard segments composed of low molecular weight diols and diisocyanates and soft segments composed of high molecular weight (long chain) diols and diisocyanates.
[0082] (e) Polyester-based elastomers include, for example, products obtained by polycondensation of dicarboxylic acid or its derivatives with diol compounds or their derivatives, and in particular products obtained by copolymerization of polyester structure and polyether structure.
[0083] (f) Polyamide elastomers, for example, include polyether block amides that use polyamides in hard segments and polyethers or polyesters in soft segments, as well as polyether ester block amides.
[0084] (g) Acrylic elastomers, with acrylates as the main component, can use ethyl acrylate, butyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, etc. Additionally, glycidyl methacrylate, allyl glycidyl ether, etc., can be used as crosslinking point monomers. Furthermore, they can also be co-polymerized with polyacrylonitrile or ethylene. Specifically, examples include acrylonitrile-butyl acrylate copolymers, acrylonitrile-butyl acrylate-ethyl acrylate copolymers, and acrylonitrile-butyl acrylate-glycidyl methacrylate copolymers.
[0085] (h) Rubber-modified epoxy resins include, for example, products obtained by modifying bisphenol F type epoxy resin, bisphenol A type epoxy resin, salicylaldehyde type epoxy resin, phenolic phenolic type epoxy resin, or cresol phenolic type epoxy resin by modifying part or all of the epoxy groups of butadiene-acrylonitrile rubber with carboxylic acids at both ends, or amino-terminated silicone rubber. Among these, styrene-based elastomers and organosilicon elastomers are preferred.
[0086] The sealing sheet 20 may contain other known additives or other ingredients without impairing the effects of the present invention. Known additives include, for example, antioxidants, weather stabilizers, heat stabilizers, lubricants, nucleating agents, ultraviolet absorbers, colorants, surfactants, and fillers. They may be used individually or in combination of two or more.
[0087] [Manufacturing method of heat sink 100]
[0088] Reference Figure 5A and Figure 5B The manufacturing method of the heat sink 100 is described in general. Figure 5A and Figure 5B This is a diagram showing the steps involved in manufacturing a heat sink.
[0089] First, a 5 wt% aqueous solution of PVA (polyvinyl alcohol) is coated onto a PET film 31 with a thickness of [50 μm] using a gravure coating machine and dried at 80°C to form a PVA layer 32. Next, an SBS solution obtained by dissolving SBS in THF (tetrahydrofuran) to a concentration of 5 wt% is coated onto the PVA layer 32 to form a sealing layer 21. This produces the laminate shown in step a1. Similarly, the laminate shown in step b1 can be produced using the same steps.
[0090] Next, using adhesive tape 33 as an adhesive strip, the sealing layer 21 and the PVA layer 32 are peeled off from the PET film 31 (step a2). Then, liquid metal (GaInSn) 110 is applied to the sealing layer 21 (step a3), and the liquid metal 110 is formed into a sheet using screen printing technology (step a4). Alternatively, the adhesive tape 33 can be, for example, a commercially available masking tape.
[0091] The tape (frame portion) 33 can be formed to surround the area where the liquid metal 110 is applied. Thus, the tape 33 functions as a mask, allowing the liquid metal 110 to be applied to the area surrounded by the tape 33. Furthermore, the liquid metal 110 is stretched into a sheet shape using screen printing technology, such that the film thickness of the liquid metal 110 corresponds to the film thickness of the tape 33. Additionally, as described above, the liquid metal 110 can be pre-mixed with 5 wt% or 10 wt% copper powder. This improves the wettability to the sealing layer 21, making it easier to form the liquid metal 110 into a sheet shape.
[0092] On the other hand, using adhesive tape 43 as an adhesive strip, the sealing layer 22 and the PVA layer 42 are peeled off from the PET film 41 (step b2). Then, the PVA layer 42 is dissolved by immersion in pure water for 5 minutes (step b3) and then adhered to the mesh layer 44 (step b4). The mesh layer 44 is used to prevent the sealing layer 22 from wrinkling, and by adhering the mesh layer 44, the laminate shown in step b4 is easy to handle.
[0093] Further, the laminates prepared in steps a1 to a4 are overlapped with the laminates prepared in steps b1 to b4, thereby sandwiching the liquid metal 110 between the sealing layer 21 and the sealing layer 22 (step c1). Then, the sealing layer 21 and the sealing layer 22 are cut between the liquid metal 110 and the adhesive tapes 33 and 34, and the portions where the adhesive tapes 33 and 34 are formed are removed (step c2). Afterward, the PVA layer 32 is dissolved, and the sealing layer 21 and the sealing layer 22 are sealed together at the periphery of the liquid metal 110, thereby completing the heat sink 100 (step c3). In addition, the mesh layer 44 shown in step c3 can be peeled off before using the heat sink 100.
[0094] Furthermore, the method of manufacturing the heat sink 100 is not limited to the method described here; the order of the steps may be changed, some steps may be omitted, or other steps may be added.
[0095] [Heater performance evaluation of Heatsink 100]
[0096] Figure 6 This is a graph representing an example of the test results for evaluating the heat dissipation performance of a heat sink (containing 5 wt% copper powder). Figure 6 The solid lines connecting the plots represent the temperature of the flexible circuit board, while the non-solid lines connecting the plots represent the temperature when a heat sink 100 is attached to the flexible circuit board.
[0097] in addition, Figure 6 The graph on the left represents the temperature under the condition of the heat sink and flexible circuit board without bending. Figure 6The graph on the right shows the temperature when the heat sink and flexible substrate are bent at a curvature of 8.5 mm.
[0098] In this experiment, heaters with metallic patterns formed near positions -7 mm, 0 mm, and 7 mm on a flexible circuit board were fabricated. Furthermore, in this experiment, a voltage of 1.0 A / 1.0 V was applied to the heaters, and their condition was measured and photographed using an infrared thermal imager.
[0099] like Figure 6 As shown, without the use of a heat sink (w / o (without) LM (Liquid Metal) Sheet), the temperature of the region in the flexible circuit board where the metal pattern is formed as a heat source rises significantly.
[0100] In addition, such as Figure 6 As shown, when using heatsink 100 (with LM Sheet: containing liquid metal sheet), temperature rise suppression is achieved in both the unbent and bent states. Figure 6 As shown, by using the heat sink 100, the temperature is approximately uniform around 40°C, and heat can be diffused in the planar direction. Thus, the heat sink 100 can also be effectively used for flexible heat-generating objects.
[0101] Figure 7 This is a graph showing an example of the test results for evaluating the heat dissipation performance of a heat sink (containing 5 wt% copper powder). Figure 7 (a) schematically represents the experimental situation. Figure 7 (b) represents an example of the test results regarding the heat dissipation performance of the heat sink.
[0102] In this experiment, such as Figure 7 As shown in (a), a heat sink 100 is attached to a flexible substrate, and an LED serving as a heat-generating element is disposed on the heat sink 100. Additionally, as... Figure 7 As shown in (b), the LED temperature change was confirmed when the LED was kept on (ON) for approximately 500 seconds and then turned off (OFF). Furthermore, the LED temperature change was also confirmed when the stretchable substrate was stretched to twice its original size.
[0103] Figure 7 The graph on the left of (b) shows the changes in LED temperature when the stretchable substrate is not stretched, when the heat sink 100 is used, and when the heat sink 100 is not used. Figure 7 The graph on the right of (b) shows the changes in LED temperature when the stretchable substrate is stretched to twice its original size, when heat sink 100 is used, and when heat sink 100 is not used.
[0104] like Figure 7 As shown in (b), in the state where the stretchable substrate is not stretched, the highest temperature without the heat sink 100 is approximately 62°C, while the highest temperature with the heat sink 100 is approximately 45°C, resulting in a temperature reduction of approximately 17°C for the LED. When the stretchable substrate is stretched to twice its original size, the highest temperature without the heat sink 100 is approximately 63°C, while the highest temperature with the heat sink 100 is approximately 43°C, resulting in a temperature reduction of approximately 20°C for the LED. Thus, the LED temperature can be reduced regardless of the stretchable substrate (heat sink 100). Furthermore, the reason for the greater temperature reduction when the substrate is stretched is believed to be that the heat sink 100 follows the shape of the stretchable substrate and becomes elongated, increasing the planar area of the liquid metal layer 10, thereby enabling more efficient in-plane heat conduction. Therefore, the heat sink 100 can be effectively used for heat-generating objects with stretchability.
[0105] [Summarize]
[0106] As described above, the heat sink 100 of this embodiment is composed of a liquid metal layer 10 that is deformable at room temperature and a sealing sheet 20 of a nano-scale thin film. Therefore, it has shape-following capability for the heat dissipation object and high heat dissipation performance. Thus, it can be used to release heat generated by heat dissipation objects that are stretchable and flexible. In addition, since the liquid metal layer 10 in the heat sink 100 is formed in a sheet shape, its in-plane thermal conductivity is high, which enables the temperature of the heat dissipation object to be reduced uniformly throughout. Furthermore, since the heat sink 100 has a tight seal on its upper and lower surfaces, it can be attached to the heat dissipation object without the need for additional adhesives. Moreover, since the liquid metal layer 10 in the heat sink 100 is sealed by the sealing sheet 20, problems such as corrosion to other metals, short circuits caused by leakage, and effects on the human body can be suppressed.
[0107] The embodiments of the present invention have been described above, but the specific structures shown in these embodiments are merely examples and are not intended to limit the technical scope of the present invention. It should be understood that those skilled in the art can make appropriate modifications to these disclosed embodiments, and the technical scope of the invention disclosed in this specification includes such modified techniques.
Claims
1. A heat sink for releasing heat generated by a heat-dissipating object, characterized in that, include: A liquid metal layer that can deform at room temperature; and A sealing sheet that seals the liquid metal layer.
2. The heat sink as described in claim 1, characterized in that: The liquid metal layer and the sealing sheet are elastic and flexible.
3. The heat sink as described in claim 1, characterized in that: The liquid metal layer contains gallium-based metals.
4. The heat sink as described in claim 1, characterized in that: The liquid metal layer contains metal powder with low reactivity to the liquid metal contained in the liquid metal layer.
5. The heat sink as described in claim 4, characterized in that: The thermal conductivity of the metal powder is higher than that of the liquid metal.
6. The heat sink as described in claim 4, characterized in that: The metal powder is copper powder.
7. The heat sink as described in claim 4, characterized in that: The metal powder comprises at least one of iron powder, nickel powder, tungsten powder, silver powder, platinum powder, and gold powder.
8. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 16 wt%.
9. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 14 wt%.
10. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 12 wt%.
11. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 10 wt%.
12. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 7 wt%.
13. The heat sink as described in claim 6, characterized in that: The weight of the copper powder relative to the total weight of the liquid metal layer is less than 5 wt%.
14. The heat sink as described in claim 1, characterized in that: The sealing sheet is a polymer nanosheet that provides a tight seal to the heat dissipation object.
15. The heat sink as described in claim 1, characterized in that: The sealing sheet is made of styrene-butadiene-styrene block copolymer.
16. The heat sink as described in claim 1, characterized in that: The sealing sheet includes a first sealing layer covering the upper surface of the liquid metal layer and a second sealing layer covering the lower surface of the liquid metal layer. The first sealing layer and the second sealing layer are tightly sealed to each other at the periphery of the liquid metal layer.
17. The heat sink as described in claim 12, characterized in that: The thickness of the first sealing layer and the second sealing layer is 100 nm or more and 500 nm or less.
18. The heat sink as described in claim 1, characterized in that: The liquid metal layer comprises a eutectic metal of gallium (Ga), indium (In), and tin (Sn) (GaInSn) and copper powder in a weight ratio of less than 5% relative to the total weight of the liquid metal layer. The sealing sheet is made of styrene-butadiene-styrene block copolymer. The sealing sheet includes a first sealing layer covering the upper surface of the liquid metal layer and a second sealing layer covering the lower surface of the liquid metal layer. The first sealing layer and the second sealing layer are tightly sealed at the periphery of the liquid metal layer. The thickness of the first sealing layer and the second sealing layer is 100 nm or more and 500 nm or less.
19. A method for manufacturing a heat sink for releasing heat generated by a heat-dissipating object, characterized in that, include: Steps for preparing the first sealing layer; The step of forming a frame on the first sealing layer in a manner that surrounds the area to be coated with liquid metal; The step of applying liquid metal to the area; The step of stretching the liquid metal coated in the region into a sheet shape in a manner corresponding to the film thickness of the frame portion; The step of setting the second sealing layer in such a way that the liquid metal is sandwiched together with the first sealing layer; The step of cutting the first sealing layer and the second sealing layer between the liquid metal and the frame portion to remove the portion forming the frame portion; and The step of sealing the first sealing layer and the second sealing layer together at the periphery of the liquid metal.
20. The method for manufacturing a heat sink as described in claim 19, characterized in that: Prior to the step of applying the liquid metal, a step of mixing metal powder into the liquid metal is included.
Citation Information
Patent Citations
Heat-radiating sheet
JP2002050725A